Fruit ordering system - Suraya, Abu Bakar; Pei Ling, Liew (2021)
Fruity Healthy application is planning to cooperate with some of t he f armers and vendors t o help them to promote their fruits through online market. In this new era, people ask for fast service. They only choose for simple and the fastest way as they do not want to queue and wait for it. Therefore, Frui ty Heal thy i s very conveni ence as t hey j ust need to use their devices and make their orders. They can either choose to buy in quantity or box.